2019
DOI: 10.1136/tsaco-2019-000306
|View full text |Cite
|
Sign up to set email alerts
|

Respect your elders: effects of ageing on intracranial pressure monitor use in traumatic brain injury

Abstract: BackgroundThe Brain Trauma Foundation recommends intracranial pressure (ICP) monitor placement for patients with severe traumatic brain injury (TBI). Adherence with these guidelines in elderly patients is unknown. We hypothesized that disparities in ICP monitor placement would exist based on patient age.MethodsUsing the National Trauma Data Bank (2010–2014), we identified patients admitted for blunt TBI with admission Glasgow Coma Scale (GCS) scores of 3–8. Patients were excluded if they had a non-Head Abbrevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…27 In a similar fashion, Schupper et al found age disparities with regard to adherence to the Brain Trauma Foundation guidelines among blunt TBI patients presenting with a GCS score of 3-8. 28 The differential effect of ICP monitoring and age on short-and long-term outcomes following severe TBI certainly merits further investigation and remains to be determined in future research. Furthermore, whether ICP monitoring contributes to lower mortality rates in severe TBI remains an area of contention among the scientific community, with the literature demonstrating conflicting results.…”
Section: Discussionmentioning
confidence: 98%
“…27 In a similar fashion, Schupper et al found age disparities with regard to adherence to the Brain Trauma Foundation guidelines among blunt TBI patients presenting with a GCS score of 3-8. 28 The differential effect of ICP monitoring and age on short-and long-term outcomes following severe TBI certainly merits further investigation and remains to be determined in future research. Furthermore, whether ICP monitoring contributes to lower mortality rates in severe TBI remains an area of contention among the scientific community, with the literature demonstrating conflicting results.…”
Section: Discussionmentioning
confidence: 98%
“… 31 There already exists age disparities in following BTF guidelines. 32 Our findings suggest this age disparity, or systematic bias, might be even more profound because the guidelines are based on a definition of severe TBI using GCS 3–8. Older adults with a true severe TBI may be underrepresented because their presenting ED GCS score may not reflect the severity of their injuries; conversely, younger adults may be overrepresented in severe TBI management guidelines, in that their TBI does not result in neurosurgical intervention or poor morbidity or mortality.…”
Section: Discussionmentioning
confidence: 80%
“…1 The volume increase of the contents in the cranial cavity makes the ICP continue to exceed 20 mm Hg, which leads to a series of symptoms and signs. 2 The continuous increase of ICP will lead to a decrease of cerebral blood flow (CBF), cerebral ischemia, and even brain death. 3 Therefore, the accurate monitoring of ICP becomes very important for the diagnosis, treatment, and prognosis of patients with craniocerebral diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Increased intracranial pressure (ICP) often occurs in patients with craniocerebral injury, cerebral hemorrhage, brain edema, brain tumor, and other neurosurgical diseases 1 . The volume increase of the contents in the cranial cavity makes the ICP continue to exceed 20 mm Hg, which leads to a series of symptoms and signs 2 . The continuous increase of ICP will lead to a decrease of cerebral blood flow (CBF), cerebral ischemia, and even brain death 3 .…”
Section: Introductionmentioning
confidence: 99%